Analysis of a catastrophic commercial coach crash based on an improved accident causation model: cause classification and lessons learned. Issue 1 (2nd January 2022) - Wang, Jianhao; Fu, Gui; Yan, Mingwei
Abstract : Introduction. This study aimed to perform an in-depth analysis of a catastrophic coach crash that occurred on the Chinese expressway, and thus draw useful lessons to avoid similar mistakes. Methods. Various causes were identified from the investigation report based on a proposed accident causation model, which provides a universal pathway for accident analysis from the individual level to the organizational level. Results. Driver error in an emergency affected by fatigue and speeding led directly to the crash. Accordingly, drivers in coaches should be monitored effectively and their unsafe acts must be corrected in a timely manner to avoid the formation of unsafe habits. Based on individual flaws, weaknesses in the construction of the organizational safety management system and safety culture were further deduced and discussed. Conclusion. The work and rest system, as well as the dynamic monitoring system for drivers, should be perfected strictly according to the regulations. Additionally, external factors regarding deficiencies in the design and management of the expressway and the supervision of the transportation company also had great impact on this crash. In summary, more efforts should be taken regarding root causes at the organizational level, regardless of internal or external factors.